Chorioptic Mange in an American Black Bear (Ursus americanus) from Massachusetts, USA - Niedringhaus, Kevin D.; Brown, Justin D.; Murray, Maureen; Oliveira, Bruno C. M. [UNESP]; Yabsley, Michael J. (Wildlife Disease Assoc, Inc, 2021)
American black bears (Ursus americanus) are increasingly reported to develop mange. This report describes a case of mange associated with a Chorioptes species, which has not previously been reported, to our knowledge, in free-ranging black bears. Basic clinical findings as well as methods of identification for this mite are provided.